Variability Among Chickpea (Cicer arietinum L.) Genotypes Subjected to Water Stress During Flowering Stage (University of Khartoum Journal of Agricultural Sciences, 2023)
The study was carried out to assess the variability for seed yieldand its components in chickpea. Twelve chickpea genotypes were evaluatedin two sowing dates (mid Nov. and mid Dec.) under two levels of watertreatments at two locations (Shambat and Shendi) during the period 2004-2008. A split-plot experiment with four replications, with main-plotsallocated for water treatment and sub-plots for the genotypes, was applied.The water levels adopted were normal irrigation (10-12 days interval) andwater stress (withholding irrigation water for three weeks during theflowering stage). The results showed that, the early sowing during Novembergave the highest; seed yield, pod number per plant and the heaviest seedweight. Likewise, normal irrigation gave the highest; seed yield, pod numberper plant, seed number per pod and seed weight, compared to the stresstreatment. Moreover, a wide range of genetic variability was detected for allcharacters at the four environments, between the two water treatments andamong the evaluated genotypes. The genotype-water interactions at the fourenvironments were significant (P